2015
DOI: 10.1590/0103-6440201300133
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Photoactivation Protocol Using Two Simultaneous Light-Curing Units for Bonding Brackets to Enamel

Abstract: photoactivation for 10 s on each proximal face of the bracket at a time; Simultaneous: photoactivation for 10 s on both proximal faces of the bracket at the same time; One side-20s: photoactivation for 20 s at one proximal face of the bracket only; and One side-10s: photoactivation for 10 s only at one proximal face of the bracket. SBS was tested immediately or after 1000 thermal cycles. Adhesive remnant index (ARI) was classified. Data were subjected to two-way ANOVA and Student-Newman-Keuls' test (α = 0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 19 In this study, no ceramic fractures were found, probably indicating that the exposure to water and temperature changes involved in thermocycling mainly affected the bond of the resin composite to the metal bracket base ( Table 4 ). 18 However, de Oliveira et al 26 reported that the bracket bond strength to enamel was significantly improved after thermocycling. Further studies are required to determine whether longer thermocycling regimens are needed.…”
Section: Discussionmentioning
confidence: 99%
“… 19 In this study, no ceramic fractures were found, probably indicating that the exposure to water and temperature changes involved in thermocycling mainly affected the bond of the resin composite to the metal bracket base ( Table 4 ). 18 However, de Oliveira et al 26 reported that the bracket bond strength to enamel was significantly improved after thermocycling. Further studies are required to determine whether longer thermocycling regimens are needed.…”
Section: Discussionmentioning
confidence: 99%